Ethics and Morality in Humanistic Studies: A Review - Saxena, Tamanna (AG Volumes, 2025)
Moral principles are the subject of ethics and morality, a branch of philosophy. The concepts of morality conceptualise human action or character as either right or wrong, good or evil. On the other hand, morals are a subjective and individual concept that varies across cultures, time, and individuals. While some people or societies see certain intentions, choices, and behaviours as moral, others may view them as immoral. The morals and ethics of humanistic studies are reviewed in this article. This review highlights the transformative role of humanistic approaches—such as reflective dialogue, values-based activities, and experiential learning—in cultivating ethical resilience, empathy, and moral reasoning. Evidence from various domains, including education and healthcare, demonstrates the integration of ethical and humanistic practices fosters compassionate, socially responsible individuals. Altruism and reciprocity theories underscore evolving moral behavior in advanced societies, while moderate ethical sensitivity among students reveals room for growth through humanistic care education. Despite progress, moral development remains context-dependent, requiring cultural, systemic, and pedagogical support. The findings affirm that nurturing morality through humanistic education is essential for societal and personal flourishing.